Application of the 3′‐noncoding region of poliovirus RNA for cell‐based regulation of mRNA stability: Implication for biotechnological applications. (21st April 2014) - Rasekhian, Mahsa; Roohvand, Farzin; Teimoori‐Toolabi, Ladan; Amini, Safieh; Azadmanesh, Kayhan
Abstract Enrichment of production yield of therapeutic proteins in mammalian cell cultures by modulation of the mRNA stability of the target protein to increase its in vivo half‐life is a new strategy in biotechnological applications. The present article describes one of the most novel approaches to modulate mRNA stability by application of 3′‐noncoding region (3′NCR) from RNA viral genome in the expression constructs. Our data indicated that although utilizing the 3′NCR sequence form poliovirus (PV‐3′NCR) downstream of the target gene might generally stabilize the secondary structure of RNA, it influenced the mRNA stability (and thereby the amount of protein production) in a cell type and time‐dependent manner, thus indicating a central role of mRNA‐stabilizing binding sites/cellular factors in this process. Our data might be of interest to the biotechnology community to improve recombinant protein production in mammalian cell cultures and RNA‐based therapy/vaccination approaches.